The Role of CTX-II , Dyslipidemia ,Vitamin D in Polycystic Ovary Syndrome - Samah Amer Hammood1 , Alaauldeen S. M. AL-Sallami (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aimed to study the serum measurement of clinical value of type II collagen (CTX-II) in syndromeof polycystic ovary in women and indicter as osteoarthritis disease marker analyzed in future levels witha recent available immune enzyme-linked sorbent assay (ELISA) kit. For increasing sensitivity test, theprotocol was modified. Levels of CTX-II increased significantly as well total protein, while decrease vitaminD and difference in lipid profile were practical between the patients compared with healthy women’s. Theobtained results suggested the monitoring interest of the serum CTX-II for the OA development in patientsof polycystic ovary syndrome in women and the relevance of the analysis of multiple time point for thisbiomarker.